Rethinking the Legal Status of Non-Muslims in Islamic Law: Al-Muwāṭinūn and the Constitutional Framework of Citizenship in Indonesia - Hermanto Harun; A. Yuli Tauvani; Nurul Hidayah Tumadi; Rusli Abdul Roni (Khazanah Hukum, 2025)
This study aims to examine the relevance of classical Islamic legal categories in defining the status of non-Muslims within the context of Indonesia’s pluralistic and democratic state. The research is motivated by recent debates surrounding the use of the term kāfir ("infidel") and the need to reassess traditional terminologies such as ahl al-dhimmah, ahl al-ḥarb, al-muʿāhid, and al-mustaʾmin in light of contemporary constitutional values. Using a qualitative approach within a library-based research design, the study analyzes classical fiqh texts and Indonesian constitutional and statutory legal documents. Through thematic content analysis, the study evaluates the compatibility of Islamic legal reasoning with modern legal principles. The findings indicate that classical classifications of non-Muslims were shaped by the political and imperial contexts of premodern Islamic governance. These categories are no longer fully applicable in the Indonesian nation-state, which is based on equality before the law and religious pluralism. In contrast, the concept of al-muwāṭinūn (citizens) aligns with the Islamic legal principle of murūnah (adaptability) and supports ijtihād (juridical reasoning) responsive to contemporary societal needs. The study contributes practically by offering a theologically grounded yet constitutionally relevant vocabulary for citizenship that enhances civic inclusion and legal equality. It demonstrates how Islamic jurisprudence can evolve to support pluralistic nationhood. This research provides an original contribution by contextualizing classical fiqh within Indonesia’s constitutional framework, an area underexplored in existing literature. By bridging Islamic legal ethics and Indonesian law, it offers a normative model for redefining non-Muslim citizenship in Muslim-majority democracies.